2000
DOI: 10.1007/bf02294183
|View full text |Cite
|
Sign up to set email alerts
|

Sample size requirements for estimating pearson, kendall and spearman correlations

Abstract: sample size, interval estimation, correlation, rank correlation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
501
0
24

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 757 publications
(533 citation statements)
references
References 23 publications
8
501
0
24
Order By: Relevance
“…24 To determine knowngroups validity, we compared the function PROMs across three subgroups of working status with a one-way ANOVA and Tukey's test post hoc. 18 A significant difference indicated that a measure could differentiate across known groups of working status.…”
Section: Reliabilitymentioning
confidence: 99%
“…24 To determine knowngroups validity, we compared the function PROMs across three subgroups of working status with a one-way ANOVA and Tukey's test post hoc. 18 A significant difference indicated that a measure could differentiate across known groups of working status.…”
Section: Reliabilitymentioning
confidence: 99%
“…It is surprising, however, that in more recent literature not much attention is given to the asymptotic variances of nonparametric correlation estimators. In Bonett and Wright (2000), for example, confidence intervals for the Spearman and Kendall correlation are constructed using approximations of the asymptotic variances, while Proposition 4 provides the closed form expressions. Most complicated is the expression for ASV(R S , Φ ρ ), requiring numerical integration of univariate integrals.…”
Section: Propositionmentioning
confidence: 99%
“…Using Wilson-θ method to calculate the multi degree of freedom shear type nonlinear seismic response, the interstory force displaement for a 3-story building is shown in Figure 2. Spearman rank correlation coefficient (SRCC)is used to study relation of the ground motion parameters and average earthquake damage index, as given by Equation 3 [8] ( The SRCCs for ground motion parameters and damge index are shown in Figure 3, for brevity only the results for PGA, PGV, PSA and Si h are shown here. It can be seen from Figure 3 and SRCCs results that the ten ground motion parameters have some correlations with the average damage index of masonry structure, and the SRCCs values for Type B masonry structure are all larger than 0.7, and larger than 0.66 for Type C buildings.…”
Section: Resultsmentioning
confidence: 99%